Surgical outcomes of subtotal colectomy with antiperistaltic caecorectal anastomosis vs total colectomy with ileorectal anastomosis for intractable slow-transit constipation. (12th May 2019) - Xie, Xiao-Yu; Sun, Kong-Liang; Chen, Wen-Hao; Zhou, Yan; Chen, Bao-Xiang; Ding, Zhao; Yu, Xue-Qiao; Wu, Yun-Hua; Qian, Qun; Jiang, Cong-Qing; Liu, Wei-Cheng
Abstract: Background: Few studies have compared the surgical outcomes of different surgical procedures currently used to treat refractory colonic slow-transit constipation (STC), despite the increase in the number of cases. This study aimed to analyse the long-term surgical outcomes of subtotal colectomy with antiperistaltic caecorectal anastomosis (SC-ACRA) vs total colectomy with ileorectal anastomosis (TC-IRA) for severe STC. Methods: Between January 2005 and January 2015, we retrospectively collected clinical data of 55 patients who underwent TC-IRA ( n = 35) or SC-ACRA ( n = 20) for severe STC at our institution. The post-operative functional outcomes between the two groups were compared. Results: There were no significant differences in age ( P = 0.655), sex ( P = 0.234), period of constipation ( P = 0.105) and defecation frequency ( P = 0.698) between the TC-IRA and SC-ACRA groups. During a median follow-up period of 72 months (range, 12–120 months), there were no significant differences between the TC-IRA and SC-ACRA groups regarding the median number of bowel movements per day [3 (1/6–7) vs 3 (1/6–5), P = 0.578], Cleveland Clinic Florida Constipation Score [2 (0–20) vs 2 (0–19), P = 0.454], Cleveland Clinic Incontinence Score [0 (0–5) vs 0 (0–2), P = 0.333] and Gastrointestinal Quality of Life Index [122 (81–132) vs 120 (80–132), P = 0.661]. Moreover, there was no significant difference in the incidence of post-operative complications between the two groups (37.1% vs 25.0%, P = 0.285). Conclusions: Our findings indicate that both TC-IRA and SC-ACRA are effective treatments for severe STC, with similar long-term outcomes.